Paleolimnological reconstruction of Late Glacial and Holocene environments of Middle Urals - A. V. Maslennikova (Литосфера, 2016)
The paleolimnological study of the Lake Tavatui sedimentary record based on a multy-proxy approach provides reconstruction of the Late Glacial and Holocene environments of the Middle Urals. Spore-pollen spectra of the Late Glacial clay reflect several climate shifts between 13.25 and 11.7 ka cal BP. Lithology, mineralogy, geochemistry and spore-pollen spectra of the lake sediment core show follows Holocene environmental changes: ?11.2 ka cal BP, ? 10.6-10.4 ka cal BP, ?9.8 ka cal BP, ? 8.5-7.5 ka cal BP, ?5.8 ka cal BP, ?4.2 ka cal BP, ?3.5 ka cal BP and ? 2.3-2.2 ka cal BP. Lake sediments accumulated since the beginning of human-induced lake level increase (1914-1915 AD) characterized by an increase in Al, K, Rb, Zr, Cs, Be, Sc, V and Ga. These lithophil elements were used as the lake-level fluctuations indicators for the Holocene lake sediments.